The Effect of Dienes Objects Strategy on 5th Grade Primary School Students’ Achievement in Arabic Grammar Subject - Mohammed Salman, Huda (Opción, 2019)
The current study aims at finding out the Effect of Dienes Objects on 5th Grade Primary School Students’ Achievement in Arabic Grammar Subject . To achieve the above aim , a null hypothesis was set which states : There is no a statistically significant difference at level of (0.05) between the mean scores of the experimen- tal group ,taught according to Dienes Objects Strategy , and the mean scores of the control one , taught according to the classical method .The sample of the study covered (115) students .distributed into four sections .A pre-test was administered and the variables were verified to secure the equivalence between the two groups of the study . The researcher has concluded that here are a statistically significant differences between the mean scores of the experimental group, and that of the control one . The researcher has conducted the t-test and the study has come up with invoking curricula designers to substitute the classical methods of teaching by modern ones that adopt effective strategies in teaching .